2020
DOI: 10.3390/agriculture10060204
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of LEDs in the Red Spectrum on the Germination, Early Seedling Growth and Antioxidant Metabolism of Pea (Pisum sativum L.) and Melon (Cucumis melo L.)

Abstract: (1) Background: In recent years, the use of light emitting diodes (LEDs) for plant production purposes has expanded. However, LEDs’ effect on seed germination and early seedling growth has been scarcely documented. (2) Methods: In this work, the effect of monochromatic red light (RL, 100 µmol m−2 s−1) for up to 60 min applied to seeds of pea and melon was analyzed in terms of seedling growth and antioxidant enzymes levels. An experimental LED chamber coupled to an electronic control system was developed for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The complexity of root phenotyping involves open-field, partially controlled greenhouse, and controlled environment agriculture in generating throughout necessary for plant breeding, genomics, and agricultural intensification (Falk et al, 2020). Morpho-agronomical characterization of root architecture has been carried out on wheat (Tomar et al, 2016), wild lettuce (L. serriola) (Fu et al, 2017), oilseed rape (Brassca napus) (Shi et al, 2013), rice (Oryza sativa L.) (Wang et al, 2020), pea (Pisum sativum L.) and melon (Cucumis melo L.) (Solano, Hernández, Suardíaz, & Barba-Espín, 2020), thale cress (Arabidopsis thaliana) (Iglesias et al, 2019;Moore et al, 2013), common bean (Phaseolus vulgaris) (Strock et al, 2019), tomato (Solanum lycopersicum L.) (Alaguero-Cordovilla, Gran-Gómez, Tormos-Moltó, & Pérez-Pérez, 2018), and corn (Zea mays) (Ghorchiani, Etesami, & Alikhani, 2018). Some seeds have a dormancy stage and cold stratification can trigger the seed membrane and promote germination.…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of root phenotyping involves open-field, partially controlled greenhouse, and controlled environment agriculture in generating throughout necessary for plant breeding, genomics, and agricultural intensification (Falk et al, 2020). Morpho-agronomical characterization of root architecture has been carried out on wheat (Tomar et al, 2016), wild lettuce (L. serriola) (Fu et al, 2017), oilseed rape (Brassca napus) (Shi et al, 2013), rice (Oryza sativa L.) (Wang et al, 2020), pea (Pisum sativum L.) and melon (Cucumis melo L.) (Solano, Hernández, Suardíaz, & Barba-Espín, 2020), thale cress (Arabidopsis thaliana) (Iglesias et al, 2019;Moore et al, 2013), common bean (Phaseolus vulgaris) (Strock et al, 2019), tomato (Solanum lycopersicum L.) (Alaguero-Cordovilla, Gran-Gómez, Tormos-Moltó, & Pérez-Pérez, 2018), and corn (Zea mays) (Ghorchiani, Etesami, & Alikhani, 2018). Some seeds have a dormancy stage and cold stratification can trigger the seed membrane and promote germination.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, the root formation of in vitro Anthurium plantlets was progressively induced under red LED lights [ 58 ]. Solano et al [ 59 ] reported that exposing pea and watermelon seedlings to red light for 15 minutes gave the highest increase in fresh weight and height, and longer exposure times decreased seedling growth. Here, there were had statistical differences between the exposure of grafted tomato seedlings to different light qualities on the shoot length, where the highest value was under red light.…”
Section: Discussionmentioning
confidence: 99%
“…292 With the ease of controlling the type of light emitted by LEDs, plant scientists and horticulturists are exploring lighting effects on plant growth, morphology, and metabolism. [295][296][297][298] This creates opportunities to intervene in plant production systems with specificity that has been impossible to accomplish in the past.…”
Section: Leds Hydroponics and Controlled Environment And Vertical Agmentioning
confidence: 99%